Indigenous leadership and governance - Domingo, Ma. Oliva Z. (Philippine Journal of Public Administration, 2004)
The success of a nation is highly dependent on the quality of its leaders. Leadership therefore continues to be an important topic for discussion in the Philippines in its quest for national development. The indigenous peoples (IPs), comprising 15 percent of the population, remain to be a significant part of the nation and have historically demonstrated their effectiveness in governing daily lives. The study discusses leadership among eight indigenous groups, identifying various titles used, sources of authority, roles and functions and the shifts from traditional to current leadership practices. It then cites lessons for current public administration scholars and practitioners alike. IP leadership structures and practices can be used in enhancing the relevance and effectiveness of formal governance process. Furthermore, political and administrative leaders may instead reflect upon the high standards of IP leadership--merit and fitness should always prevail.